Evolution of sex allocation plasticity in a hermaphroditic flatworm genus. (18th May 2022) - Singh, Pragya; Schärer, Lukas
Abstract: Sex allocation theory in simultaneous hermaphrodites predicts that optimal sex allocation is influenced by local sperm competition, which occurs when related sperm compete to fertilize a given set of eggs. Different factors, including the mating strategy and the ability to self‐fertilize, are predicted to affect local sperm competition and hence the optimal SA. Moreover, since the local sperm competition experienced by an individual can vary temporally and spatially, this can favour the evolution of sex allocation plasticity. Here, using seven species of the free‐living flatworm genus Macrostomum, we document interspecific variation in sex allocation, but neither their mating strategy nor their ability to self‐fertilize significantly predicted sex allocation among these species. Since we also found interspecific variation in sex allocation plasticity, we further estimated standardized effect sizes for plasticity in response to (i) the presence of mating partners (i.e. in isolation vs. with partners) and (ii) the strength of local sperm competition (i.e. in small vs. large groups). We found that self‐fertilization predicted sex allocation plasticity with respect to the presence of mating partners, with plasticity being lower for self‐fertilizing species. Finally, we showed that interspecific variation in sex allocation is higher than intraspecific variation due to sex allocation plasticity. Our study suggests that both sex allocation and sex allocation plasticity are evolutionarily labile, with self‐fertilization predicting the latter in Macrostomum . Abstract : Interspecific variation in both sex allocation and sex allocation plasticity in the hermaphroditic flatworm genus Macrostomum, including among closely related species, suggests that both sex allocation and sex allocation plasticity are evolutionarily labile. Moreover, self‐fertilization, but not mating strategy, predicts the evolution of sex allocation plasticity in Macrostomum .